2021
DOI: 10.1186/s12871-021-01350-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous oxycodone on the physiologic responses to extubation following general anesthesia

Abstract: Background Endotracheal intubation and extubation may cause undesirable hemodynamic changes. Intravenous oxycodone has recently been introduced and used for relieving hemodynamic alterations in response to intubation, but there is insufficient information regarding its application in stabilizing hemodynamics during extubation in the patients emerging from general anesthesia. Methods One hundred patients, who had undergone assorted laparoscopic surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The definition of active extubation was the patient tried to pull the tracheal tube out by hand, but it was not pulled out (special staff ensured that the tube was not removed) during recovery from anaesthesia. The definition of postoperative cough was more than 5 spontaneous coughs that lasted longer than 5 s within the first 24 h after extubation, as previously described [ 10 ]. Cardiovascular reactions prior to extubation included systolic blood pressure (SBP) (mmHg), diastolic blood pressure (DBP) (mmHg), heart rate (HR) (beats/min), plasma concentrations of epinephrine (E) (pmol/l) and norepinephrine (NE) (pmol/l).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of active extubation was the patient tried to pull the tracheal tube out by hand, but it was not pulled out (special staff ensured that the tube was not removed) during recovery from anaesthesia. The definition of postoperative cough was more than 5 spontaneous coughs that lasted longer than 5 s within the first 24 h after extubation, as previously described [ 10 ]. Cardiovascular reactions prior to extubation included systolic blood pressure (SBP) (mmHg), diastolic blood pressure (DBP) (mmHg), heart rate (HR) (beats/min), plasma concentrations of epinephrine (E) (pmol/l) and norepinephrine (NE) (pmol/l).…”
Section: Methodsmentioning
confidence: 99%
“…SBP, DBP, and HR were measured with a monitor. Blood samples were collected immediately before extubation and 1 min after extubation from the arm without an intravenous infusion, according to a previous report [ 10 ]. Concentrations of epinephrine and norepinephrine, were measured using a commercially available ELISA kit (IBL, Germany) and an ELISA plate reader (BioTek, Winooski, VT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Studies on exploring the effectiveness and safety of oxycodone for general anesthesia tracheal intubation have shown that oxycodone has less effect on blood pressure and heart rate than fentanyl and has a relatively smooth circulation[ 52 , 54 - 56 ]. Another issue to consider with oxycodone as an induction drug is its effect on anesthetic awakening and extubation.…”
Section: New Advances In Clinical Applicationsmentioning
confidence: 99%
“…The de nition of active extubation: the patient has the behavior of pulling out the tracheal tube by hand, but it is not pulled out (we have special staff to take care of it, and we will not let it happen) during recovery from anesthesia. The de nition of postoperative cough: spontaneous coughing more than 5 times and lasted longer than 5 s within the rst 24 h after extubation, as the previous assessments described [9].…”
Section: Parameter Measurementmentioning
confidence: 99%
“…The SBP, DBP, and HR were measured with a monitor. Blood samples were collected at immediately before extubation and one minute after extubation, from the arm that was not on intravenous infusion, according to previous reports [9]. Concentrations of blood hormones including epinephrine and norepinephrine were measured by ELISA using commercially available kit (IBL, Germany) and ELISA plate reader (BioTek, Winooski, VT, USA).…”
Section: Parameter Measurementmentioning
confidence: 99%